(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Annotation: Purpose of the study: To study the correlation of the middle part of the face with congenital cleft lip and palate after surgical procedures. Material and research methods. 630 children of the I and II periods of childhood with CCLP at the age of 3 to 12 years were examined. Among them, 390 (61.9%) boys, 240 (38.1%) girls who underwent surgical manipulation depending on the severity of the anomaly of the lip and palate in the Department of Maxillofacial Surgery at the Bukhara Children's Multidisciplinary Medical Center in Bukhara in the period from 2009 by 2018. Results and discussion. To solve this goal, a morphometric study was carried out and morphometric parameters of the craniofacial region of children of the I and II period of childhood with CCLP were obtained, clinical and anthropometric methods were used, followed by statistical processing of the data. When performing this work, the methodology of anthropometric studies of children was used on the methodological recommendation of N. Kh. Shomirzaev, S. A. Ten and S. I. Tukhtanazorova (1998). Conclusion. In order to increase the efficiency of the physical development of special children, that is, children with CCLP, it is necessary after surgical interventions to conduct a continuous anthropometric measurement of the craniofacial region of children by communicating with specialists as pediatricians, therapists, orthopedists dentists and maxillofacial surgeons. Only in this case can the desired result be achieved in accordance with the principle of the golden ratio.